Ischaemic spinal cord injury after cardiac surgery. Issue 6 (June 1985) - Puntis, J W; Green, S H
Abstract : The case records of eight children with an acute spinal cord lesion after cardiac surgery were reviewed. All had been operated on for congenital heart disease over the past 10 years. The prognosis for neurological recovery was poor and scoliosis and bladder dysfunction were common complications. Ischaemic cord injury is usually associated with coarctation of the aorta but may occur when surgery is performed for other cardiovascular defects.